2020
DOI: 10.1186/s12913-020-05856-5
|View full text |Cite
|
Sign up to set email alerts
|

Health care utilization and HIV clinical outcomes among newly enrolled patients following Affordable Care Act implementation in a California integrated health system: a longitudinal study

Abstract: Background The Affordable Care Act (ACA) has increased insurance coverage for people with HIV (PWH) in the United States. To inform health policy, it is useful to investigate how enrollment through ACA Exchanges, deductible levels, and demographic factors are associated with health care utilization and HIV clinical outcomes among individuals newly enrolled in insurance coverage following implementation of the ACA. Methods Among PWH n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Studies, however, reported that after the ACA was implemented, certain racial/ethnic and gender-specific groups such as Black women and men have continued to experience increased rates of unmet needs and continue to comprise the most disadvantaged groups [ 30 ]. Another study that investigated the association between ACA enrollment, deductibles, healthcare utilization, and clinical outcomes for HIV patients found that Black and Hispanic individuals living with HIV experienced suboptimal HIV outcomes [ 31 ]. Thus, these mixed results highlight the need to examine healthcare utilization patterns among specific subgroups of racial and ethnic minorities.…”
Section: Introductionmentioning
confidence: 99%
“…Studies, however, reported that after the ACA was implemented, certain racial/ethnic and gender-specific groups such as Black women and men have continued to experience increased rates of unmet needs and continue to comprise the most disadvantaged groups [ 30 ]. Another study that investigated the association between ACA enrollment, deductibles, healthcare utilization, and clinical outcomes for HIV patients found that Black and Hispanic individuals living with HIV experienced suboptimal HIV outcomes [ 31 ]. Thus, these mixed results highlight the need to examine healthcare utilization patterns among specific subgroups of racial and ethnic minorities.…”
Section: Introductionmentioning
confidence: 99%